Food irradiation : a reference guide - Wilkinson, V. M. (Woodhead Publishing series in food science and technology., 1998)
This reference guide is applicable to the food industry, research institutions, academia, and trade and consumer organisations. Contents include: Introduction (trends in food spoilage and safety, food preservation technologies, the use of ionising radiation); Food irradiation topics (from additives to yoghurt); List of entries by category (including listing by food groups and components, control of microbiological hazards and irradiation methods).